2016
DOI: 10.1038/srep31787
|View full text |Cite
|
Sign up to set email alerts
|

Head movement, an important contributor to human cerebrospinal fluid circulation

Abstract: The suboccipital muscles are connected to the upper cervical spinal dura mater via the myodural bridges (MDBs). Recently, it was suggested that they might work as a pump to provide power for cerebrospinal fluid (CSF) circulation. The purpose of this study was to investigate effects of the suboccipital muscles contractions on the CSF flow. Forty healthy adult volunteers were subjected to cine phase-contrast MR imaging. Each volunteer was scanned twice, once before and once after one-minute-head-rotation period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 32 publications
3
64
0
Order By: Relevance
“…Considering the location of attachment of the myodural bridge to the dorsal spinal dura mater, adjacent to the cerebello‐medullary cistern, which is the largest subarachnoid cistern, we presume that the myodural bridge functions to maintain the integrity of the cerebello‐medullary cistern (Scali et al, , ) and that the contraction of the myodural bridge via the rectus capitis dorsalis minor muscle may have a function that is related to the circulation of the cerebrospinal fluid (Sui et al, ; Xu et al, ). A biomechanical study has demonstrated that the contraction of the rectus capitis posterior minor muscle causes posterior displacement of the dura mater via the myodural bridge (Venne et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the location of attachment of the myodural bridge to the dorsal spinal dura mater, adjacent to the cerebello‐medullary cistern, which is the largest subarachnoid cistern, we presume that the myodural bridge functions to maintain the integrity of the cerebello‐medullary cistern (Scali et al, , ) and that the contraction of the myodural bridge via the rectus capitis dorsalis minor muscle may have a function that is related to the circulation of the cerebrospinal fluid (Sui et al, ; Xu et al, ). A biomechanical study has demonstrated that the contraction of the rectus capitis posterior minor muscle causes posterior displacement of the dura mater via the myodural bridge (Venne et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies by Yuan et al () revealed that patients of chronic cervicogenic headache have a hypertrophic M. rectus capitis posterior minor and that the myodural bridge may be implicated in this type of headache. Other hypothesized functions of the myodural bridge is the maintaining of the integrity of the cerebello‐medullary cistern (Scali et al, ; Scali, Pontell, Nash, & Enix, ) and acts as a cerebrospinal fluid pump (Hallgren, Hack, & Lipton, ; Sui et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, its functional role through the MDB is still not fully elucidated [2]. Several reports have shown that changes in the SA of the RCPmi muscle are correlated with the severity of cervicocephalic pain syndrome, mTBI and headache syndrome [10][11][12][13][14]. Accordingly, it is crucial to accurately document the SA of the RCPmi to determine its influence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently confirmed as a conserved structure in mammals [7][8][9]. The MDB has a critical role in transmitting tensile force from its muscular and ligamentous components to the SDM, which has an essential role in the etiology of headache and cervicocephalic pain syndrome [10][11][12][13][14]. The rectus capitis posterior minor (RCPmi) was the first suboccipital muscle identified to attach to the dorsal cervical SDM at the posterior atlanto-occipital (PAO) interval [1].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure changes may also be contributed by the cardiac [135,160] and respiratory cycles [160,161]. Interestingly, bodily movement temporally changes the direction of CSF flow in humans [162] and in the zebrafish brain ventricular system [32]. Since many physiological parameters impact the bulk flow, and are difficult to measure with high spatial and temporal resolution, most studies focus on the cilia-mediated flow along the ventricular walls.…”
Section: Regulation Of the Csf Flowmentioning
confidence: 99%